2022
DOI: 10.14330/cwr.2022.8.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Outward FDI: Determinants and Flows in Emerging Economies: Evidence from China

Abstract: Outward Foreign Direct Investment (OFDI) is the cross-border capital flow with the objective of the long-term association having at least a ten percent stake in the equity of the host country firm. In the case of new investment, the total equity is OFDI. This research aims to analyze OFDI in the context of China. The lasting interest is considered 10% equity, thereby saying that if the cross-border investment is at least 10% of the equity share capital, the investment would be considered FDI; if below 10%, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Because of the unique laws regulating financial sector firms and in line with the previous research, these deals were excluded from the sample. A minimum cut-off of 10% of stakes acquired was applied to exclude foreign portfolio investments ( World Investment Report 2000: Cross-Border Mergers and Acquisitions and Development , UNCTAD , 2000; Zreik et al , 2022). As the study uses event study methodology, availability of acquirer stock prices for the estimation and event window is essential for a deal to be retained in the final sample.…”
Section: Data and Research Methodsmentioning
confidence: 99%
“…Because of the unique laws regulating financial sector firms and in line with the previous research, these deals were excluded from the sample. A minimum cut-off of 10% of stakes acquired was applied to exclude foreign portfolio investments ( World Investment Report 2000: Cross-Border Mergers and Acquisitions and Development , UNCTAD , 2000; Zreik et al , 2022). As the study uses event study methodology, availability of acquirer stock prices for the estimation and event window is essential for a deal to be retained in the final sample.…”
Section: Data and Research Methodsmentioning
confidence: 99%
“…In terms of consumer behaviour, study conducted by Zreik et al (2022) showed a significant change, with less money being spent on non-essential items and services. Income cuts and job losses caused by businesses cutting back or going out of business contributed to this change.…”
Section: Literature Reviewmentioning
confidence: 99%